2023
DOI: 10.3390/plants12020257
|View full text |Cite
|
Sign up to set email alerts
|

Traditional, Therapeutic Uses and Phytochemistry of Terrestrial European Orchids and Implications for Conservation

Abstract: The Orchidaceae family accounts for about 28,000 species, and most of them are mentioned in the folk medicine of nations around the world. The use of terrestrial orchids in European and Mediterranean regions has been reported since ancient times, but little information is available on their medicinal properties, as well as on their phytochemicals and biological activities. However, plant collection for human use is still listed as one of the main threats for terrestrial orchids, alongside other menacing factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 189 publications
0
8
0
Order By: Relevance
“…The results of DNA barcoding using applied markers revealed that salep samples from northwestern Greece represent nine members of four different genera of Orhidaceae (Figure 1). Other review studies [8] reported as many as 46 tuberous and 1 rhizomatous orchid species used for salep in the European context, up to 90 different taxa in Turkey [10], and up to 38 species from 7 genera in Iran [12,13]. Nonetheless, it seems that members of specific genera such as Orchis, Anacamptis, and Ophrys in addition to Dactylorhiza, Himantoglossum, Neotinea, Platanthera, and Serapias are usually common between different regions [8].…”
Section: Consensus and Explanation Cases Reasonmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of DNA barcoding using applied markers revealed that salep samples from northwestern Greece represent nine members of four different genera of Orhidaceae (Figure 1). Other review studies [8] reported as many as 46 tuberous and 1 rhizomatous orchid species used for salep in the European context, up to 90 different taxa in Turkey [10], and up to 38 species from 7 genera in Iran [12,13]. Nonetheless, it seems that members of specific genera such as Orchis, Anacamptis, and Ophrys in addition to Dactylorhiza, Himantoglossum, Neotinea, Platanthera, and Serapias are usually common between different regions [8].…”
Section: Consensus and Explanation Cases Reasonmentioning
confidence: 99%
“…The commercial product commonly called 'salep' ('salepi' in Greek) is the most famous folk preparation comprising orchids [8]. For thousands of years, terrestrial orchids in the Eastern Mediterranean and the Balkans have been harvested to ground their tubers to produce the famous salep powder [7,[9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations